Search for anomalous production of events with a photon, jet, b-quark jet, and missing transverse energy - Aaltonen, T; Adelman, J; Akimoto, T; Alvarez Gonzalez, B; Amerio, S; Amidei, D; Anastassov, A; Annovi, A; Antos, J; Apollinari, G; Apresyan, A; Arisawa, T; et al. (2009)
We present a signature-based search for the anomalous production of events containing a photon, two jets, of which at least one is identified as originating from a b quark, and missing transverse energy (E T). The search uses data corresponding to 2.0fb-1 of integrated luminosity from pp̄ collisions at a center-of-mass energy of s=1.96TeV, collected with the CDF II detector at the Fermilab Tevatron. From 6.69747×106 events with a photon candidate with transverse energy ET>25GeV, we find 617 events with E T>25GeV and two or more jets with ET>15GeV, at least one identified as originating from a b quark, versus an expectation of 607±113 events. Increasing the requirement on E T to 50 GeV, we find 28 events versus an expectation of 30±11 events. We find no indications of non-standard-model phenomena. © 2009 The American Physical Society.